Financial reform in socialist economies - Kessides, Christine, 1953- (EDI seminar series, 1989)
Revised and edited papers presented at a Workshop on Financial Reform in Socialist Economies held at the European University Institute (EIU), Florence in October 1987 -- Foreword.